Georgia Architectural and Historic Properties Survey of 803 W. Magnolia St., Valdosta, Ga. - Smith, Bartholomew; Smith, Freda (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 803 W. Magnolia St., Valdosta, Ga. One and a half story brick house with high gabled roof. Gabled dormer with double hung sash windows with 3/1 lights. Interior & exterior chimneys. Rectangular plan. Pediment over entrance. Double hung sash windows with 3/1 lights. Fair condition. Date of Construction: App. 1925. Has significance as part of a potential N.R. district.
1 electronic record and derivatives. 1 PDF. 3 scans. 82.7 MB (86,751,224 bytes). 1 photograph digitized from original negative. 2400 DPI TIF. 300 DPI 4x6 JPG.
Keywords: Electronic records; Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)